The moderate substitution of Astragalus sinicus returning for chemical fertilizer improves the N cycle function of key ecological bacterial clusters in soil - Lv, Minghao; Wang, Yongdong; Chen, Xiaofen; Qin, Wenjing; Shi, Wencong; Song, Weifeng; Chen, Jingrui; Xu, Changxu (Frontiers in Microbiology, 2023)
Astragalus sinicus (Chinese milk vetch) is a well-established resource of organic fertilizer widely used in paddy soil to partially replace chemical fertilizers. However, the influence of returning A. sinicus to fields on the soil bacterial community remains poorly understood. Here, we used different amounts of A. sinicus partially replacing chemical fertilizers and investigated the changes in soil physicochemical factors and the soil bacterial community structure responses. Returning A. sinicus to the field significantly increased the soil total nitrogen and available phosphorus content (p < 0.05). Weighted gene correlation network analysis (WGCNA) was applied to detect significant associations between the soil microbiome data and physicochemical factors. Two key ecological bacterial clusters (MEturquoise and MEgreen), mainly containing Acidobacteria, Proteobacteria, and Chloroflexi, were significantly correlated with soil nitrogen (N) levels. A. sinicus partially replacing chemical fertilizers reduced the normalized stochasticity ratio (NST) of rare amplicon sequence variants (ASVs), abundant ASVs, MEturquoise, and MEgreen (p < 0.05). Our results further indicated that a moderate amount of A. sinicus returned to the soil effectively mitigated the trend of reduced relative abundance of N fixation function of key ecological clusters caused by chemical fertilizer. However, a large amount of A. sinicus led to a significant increase in relative abundance of denitrification function and a significant decrease in relative abundance of N fixation function of key ecological clusters. This implies that the moderate substitution of A. sinicus returning for chemical fertilizer improves the N cycling function of key ecological bacterial clusters in soil. From the perspective of the bacterial community in paddy soil, this study provides new insight and a reference on how to find a good balance between the amount of A. sinicus returned to the soil and ecological safety.